2020
DOI: 10.1085/jgp.201912502
|View full text |Cite|
|
Sign up to set email alerts
|

Differential regulation of BK channels by fragile X mental retardation protein

Abstract: Fragile X mental retardation protein (FMRP) is an RNA-binding protein prominently expressed in neurons. Missense mutations or complete loss of FMRP can potentially lead to fragile X syndrome, a common form of inherited intellectual disability. In addition to RNA regulation, FMRP was also proposed to modulate neuronal function by direct interaction with the large conductance Ca2+- and voltage-activated potassium channel (BK) β4 regulatory subunits (BKβ4). However, the molecular mechanisms underlying FMRP regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
(100 reference statements)
1
22
0
Order By: Relevance
“…The R138Q mutation does not affect the role of FMRP in translation regulation (16,24). Therefore, its ability to rescue defective ADBE in KO neurons supports the hypothesis that presynaptic defects observed in the absence of FMRP are translation-independent (15).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The R138Q mutation does not affect the role of FMRP in translation regulation (16,24). Therefore, its ability to rescue defective ADBE in KO neurons supports the hypothesis that presynaptic defects observed in the absence of FMRP are translation-independent (15).…”
Section: Discussionmentioning
confidence: 58%
“…We exploited the ability of WT FMRP to rescue TMR-dextran uptake to perform molecular replacement studies using two loss of function mutants: FMRP I304N -that does not bind ribosomes (De Boulle et al, 1993) and FMRP R138Q -that does not bind BK channels (Kshatri et al, 2020;Myrick et al, 2015) ( Figure 4C). When these experiments were performed, FMRP WT restored TMR-dextran uptake in Fmr1 KO cultures as previously observed ( Figure 4D).…”
Section: Bk Channel Activation Corrects Adbe Defects In Fmr1 Ko Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, FMRP is thought to increase the open probability of type II BK channels by binding to their auxiliary β 4 subunits, thereby modifying neuronal action potentials and neurotransmission (1,2). In this issue of JGP, Kshatri et al demonstrate that FMRP also regulates type I BK channels lacking β subunits, indicating that the effects of FMRP on BK currents are more complex than originally thought (3).…”
mentioning
confidence: 99%
“…FMRP also clustered with BKαβ 4 channels, but its effects on this type of BK channel were relatively modest, only slowing the rate of deactivation by a factor of ∼2. Kshatri et al found that, rather than abrogating the effects of β 4 by sequestering it, FMRP potentiates β 4 function: while β 4 enhances voltage sensor activation in BKα channels, FMRP promotes pore opening to further enhance channel activity (3).…”
mentioning
confidence: 99%